Analysis of the economic feasibility of organic polyculture - Alves, Luiz Emílio Vicentin; Araújo Neto, Sebastião Elviro; Negreiros, Jacson Rondinelli da Silva; Andrade Neto, Romeu de Carvalho; Siviero, Amauri (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2018)
The polyculture systems guarantees food to small farmers, would ensure sustainable agriculture, high productivity per unit area and lessen the natural risks of agriculture. Within this context the objective of this study was to evaluate the production cost and profitability of an organic polyculture system comprising passion fruit, maize, pineapple and cassava in association with the cover crops. This research was carried out at the Seridó Ecological Farm, in the Municipality of Rio Branco, Acre State, from 2009 to 2011, in the completely randomized block design in a split plot arrangement with three repetitions and comprised plots containing passion fruit supported by espaliers located 3 m or 4 m apart. Plots were divided into subplots containing the cover crops jack-bean, crotalaria, tropical kudzu, peanut forage or spontaneous plants (treatments), and maize. The pineapple and cassava were planted between the espaliers. The effects of different cover crops were not so evident in plots with 3 m-spaced espaliers (P < 0.05) which increased productivity and production cost, providing a lower cost benefit ratio. The organic polyculture of passion fruit with pineapple, maize and cass in plots with 4 m-spaced espaliers, with the soil covered by jack bean increased total and net revenue, cost benefit ratio and economic feasibility.